2014
DOI: 10.1159/000362935
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Treatment of Stereotactic Cyst Aspiration and Radiosurgery for Cystic Brain Metastases

Abstract: Background: Surgical removal is the first choice of treatment for large cystic brain metastases. However, some patients cannot undergo surgical resection due to their general condition and/or the tumor location. Aims: In this study, we investigated the feasibility and safety of stereotactic cyst aspiration and gamma knife radiosurgery (GKR) as an alternative treatment for these lesions and followed the volumetric changes in cystic and solid portions. Methods: Between February 2005 and March 2012, a total of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…Tumor control is an important aspect of this treatment. The overall local tumor control of the aspirated cystic lesions after GKRS was 60.9%, which is within the range of other studies reporting a tumor control of 54.2-91.7% [2,3,5,9,15,19,20]. The local tumor progression was 39.1% which is in line with others reporting a local tumor progression of 8.3-41.4% [2,3,5,9,15,19,20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Tumor control is an important aspect of this treatment. The overall local tumor control of the aspirated cystic lesions after GKRS was 60.9%, which is within the range of other studies reporting a tumor control of 54.2-91.7% [2,3,5,9,15,19,20]. The local tumor progression was 39.1% which is in line with others reporting a local tumor progression of 8.3-41.4% [2,3,5,9,15,19,20].…”
Section: Discussionsupporting
confidence: 87%
“…The mean volumetric decrease was 56.5% after SCA which is within the range of other studies reporting a mean volumetric decrease of 47.8-77.9% [2,3,5,15] after SCA. A great advantage of cyst aspiration is acute symptomatic relief due to mass reduction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, Franzin et al (6) found that no acute complications were observed and that only 7.6% of patients underwent radionecrosis following treatment with GKRS combined with stereotactic aspiration for cystic brain metastases. Jung et al (22) reported that stereotactic cyst aspiration and radiosurgery for cystic brain metastases resulted in a local control rate of 58.6%; this type of treatment is safe, but the efficiency is not high. In the present study, 10 cases of phosphorus-32 radiotherapy patients without radioactive brain necrosis were also recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, most of these lesions derived from lung cancer and these had the highest incidence of BM and the most cystic BM patients published [8, 9, 15]. Patients with non-small-cell lung cancer (NSCLC) harboring anaplastic lymphoma kinase (ALK)-rearrangements that were treated with crizotinib have also presented with cystic BM [1619].…”
Section: Discussionmentioning
confidence: 99%